2019
DOI: 10.3390/cells8101156
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of TLE3 in Sertoli Cells of the Testes during Postnatal Development

Abstract: Spermatogenesis is a process by which haploid cells differentiate from germ cells in the seminiferous tubules of the testes. TLE3, a transcriptional co-regulator that interacts with DNA-binding factors, plays a role in the development of somatic cells. However, no studies have shown its role during germ cell development in the testes. Here, we examined TLE3 expression in the testes during spermatogenesis. TLE3 was highly expressed in mouse testes and was dynamically regulated in different cell types of the sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…In addition, since Tle3 has been reported to be associated with male reproduction ( Lee et al., 2019 ), we next asked whether the exon 7/8 skipping alters the reading frame of Tle3 mRNA and TLE3 protein expression in spermatogonia. We first utilized ORF FINDER to predict the open reading frame (ORF) of the Tle3 exon-skipped isoform and found that the reading frame of Tle3 mRNA was affected after undergoing AS ( Figure S6 I).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, since Tle3 has been reported to be associated with male reproduction ( Lee et al., 2019 ), we next asked whether the exon 7/8 skipping alters the reading frame of Tle3 mRNA and TLE3 protein expression in spermatogonia. We first utilized ORF FINDER to predict the open reading frame (ORF) of the Tle3 exon-skipped isoform and found that the reading frame of Tle3 mRNA was affected after undergoing AS ( Figure S6 I).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we identified an intriguing gene, Tle3 , on whose transcripts UHRF1 is enriched and regulates its exon skipping, suggesting that UHRF1 may bind to Tle3 and thus contribute to its pre-mRNA splicing. Although Tle3 has been reported to serve as an essential regulator in Sertoli cells and is highly expressed in spermatogonia, its role during spermatogenesis, especially in spermatogonia, is largely unknown ( Lee et al., 2019 ). Given that we have demonstrated that UHRF1 affects the transcription of Tle3 and binds to its mRNA to regulate AS, we speculate that Tle3 is a critical downstream factor of UHRF1 and may shoulder the responsibility of SSC homeostasis.…”
Section: Discussionmentioning
confidence: 99%
“…TLE3, a transcriptional co-regulator that interacts with DNA-binding factors, plays a role in the development of somatic cells. Lee et al [34] revealed that TLE3 is differentially expressed in Sertoli cells and plays a crucial role in regulating cell-specific genes involved in the differentiation and formation of Sertoli cells during testicular development. Huang et al [35] found that MGAT1 was expressed at lower levels in mouse all germ-cell types, as well as somatic Sertoli cells.…”
Section: Discussionmentioning
confidence: 99%